Menganalisis Karakteristik Lingkungan Inklusif Di Sekolah Umum Bagi Anak Berkebutuhan Khusus - Ibnu Kharis Alfauzi; Wafiq Azizah; Rabiatul Adawiyah; Opi Andriani (Universitas Maritim AMNI Semarang, 2024)
The aim of preparing this article is to analyze inclusion and an inclusive, learning-friendly environment in public schools. The research used interview and direct observation methods at SDN 196/II Taman Agung and SDN 224/II Sijau. Inclusion is a form of equality and a form of realizing education without discrimination where children with special needs and children in general can receive the same education. Meanwhile, an inclusive environment that is friendly to learning can be interpreted as involving all students without exception.